Predicting Credit Risks: Using Sustainability Criteria into Credit Risk Management - Oswari, Teddy (International Research Journal of Business Studies, 2008)
Many researchers have reported that there is a correlation between a company’s environmental performances with its financial performance. The role of criteria pertaining to sustainability and environmental orientation could play important roles in credit risk management process. The sustainability criteria can be used to predict financial performance of a debtor and, thus, improve predictive ability of a credit rating process. This article tests the relationship by using three sustainability measures as independent variables and traditional rating as dependent variable in a stepwise regression model. The result shows improvement in prediction. However, the use of additional criteria will increase cost in the prediction process. Further cost-benefit analysis related to the addition of those criteria would be valuable for credit risk management practices.